The synthesis and hydration of ternesite, Ca5(SiO4)2SO4. (November 2018) - Skalamprinos, Solon; Jen, Gabriel; Galan, Isabel; Whittaker, Mark; Elhoweris, Ammar; Glasser, Fredrik
Abstract: The hydration and strength evolution of two multi-phase ternesite-based cements with 15 and 29 wt% ternesite are reported. The synthesis and hydration properties of single phase ternesite, nominally Ca5 (SiO4 )2 SO4, are also reported including both chemically-pure ternesite and preparations doped with sodium, potassium, phosphorous, magnesium, manganese, strontium, zinc and titanium oxides. Hydration of the samples at 25 °C was studied by calorimetry and quantitative X-ray diffraction. Unconfined compressive strength development was determined for up to 1 year. Single-phase chemically activated ternesite hydrated rapidly at 25 °C achieved compressive strengths of ≈30 and ≈65 MPa at 28 and 90 days respectively, with C-S-H and gypsum as hydration products. The multi-phase ternesite-based cements reached 7 day strengths of ≈30 MPa. It is concluded that ternesite reacts with water, exhibiting strength gain. The future of calcium sulfoaluminate and sulfosilicate cements is discussed and it is suggested that a considerable, and as yet unrealised scope exists for simultaneously optimising cementing properties while lowering production costs and reducing CO2 emissions.